Set-style yoghurts made from goat milk bases fortified with whey protein concentrates. Issue 3 (19th August 2019) - Zoidou, Evangelia; Theodorou, Sofia; Moschopoulou, Ekaterini; Sakkas, Lambros; Theodorou, Georgios; Chatzigeorgiou, Artemi; Politis, Ioannis; Moatsou, Golfo
Abstract: This research paper addresses the hypothesis that the fortification of goat milk base with whey protein concentrate (WPC) could affect both the textural and the biofunctional properties of set-style yoghurt. The effect of fortification of goat milk base with two different WPCs on thermophilic bacteria counts, proteolysis, physical and biofunctional properties of set-style yoghurts was studied at specific sampling points throughout a 4-week storage period. Fortification and storage did not influence thermophilic counts. Physical properties were affected significantly ( P < 0.05) by the composition of the protein and the mineral fraction of the WPC but not by the storage. ACE-inhibitory activity was moderate in accordance to low lactobacilli counts and lack of proteolysis. DPPH-radical scavenging activity, Fe 2+ -chelating activity and superoxide scavenging activity were high. At 28 d an anti-inflammatory effect was observed, which was not affected by WPC addition.